Diversity & empire: Baltic Germans & comparative development - Alise Vitola; Theocharis Grigoriadis (Freie Universität Berlin, School of Business & Economics, 2018)
In this paper, we explore the long-run effects of cultural and imperial legacies in the Baltic region. Drawing evidence from the 1897 population census in the Russian Empire, we find that localities with a higher share of German historical population are inclined to be more developed in contemporary Latvia and Estonia. Furthermore, based on the Life-In-Transition Survey (LiTS), we use robust regression discontinuity and identify persistent differential patterns of socioeconomic and political preferences across the borders of the former imperial territories of Estland, Livonia (Swedish Livonia), Letgallia (Polish Livonia) and Courland. Hence, we argue for the persistence of legacies as drivers of divergent development paths in the regions of Latvia and Estonia.
Keywords: N43; O57; P51; 330; Baltic Germans; diversity; empire; development; culture